PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PENGGUNA DOMPET DIGITAL GO-PAY DI DKI JAKARTA - Tita Claudia Aprilia, (2020)
The development of technology and information that is growing rapidly and is supported by technological advances in theuse of mobile phnes connected to the interet led to ncreased competition in the growth of eectronic money (e-money). Due to the emergence of various types of electronic money, this opens up opportunities for electronic money businesses to cotinue to innovate by improving the quality of service to acieve customer satisfaction. Thisi study aims to determine the effect of quality on customer satisfaction. The population in this study are user digital wallet go-pay in DKI Jakarta. The.sampling method ued was purpoosive sampling, with atotal sample of 60 respondents. Respondent data is collected by distributing questionaires online. This study uses SmartPLS 3.0 (Partial Least Square) as an analysis tool. The findins from the reults of this analysis show that service quality viewed from the tangible dimensions, reliability and assurance effect on customer satisfaction while responsieness and empathy have no efect on customer satisfaction user digital wallet go-pay in DKI Jakarta.